Cognitive, social, emotional, and subjective health benefits of computer use in adults: A 9-year longitudinal study from the Midlife in the United States (MIDUS) - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2020)
Computer use has been proposed to carry a host of benefits for cognitive function and socioemotional well-beingin older adults. However, the literature on computer use remains equivocal as extant research suffers from mixedfindings as well as methodological limitations, such as overreliance on cross-sectional designs, small samplesizes, and use of narrow criterions. The current studies (NStudy 1 ¼ 3,294, NStudy 2 ¼ 2,683) sought to address theselimitations through the use of a large-scale, nationally representative, and longitudinal dataset. We found thatfrequency of computer use—over a period of approximately 9 years—longitudinally predicted positive changesin executive functioning, hedonic well-being, eudaimonic well-being, sense of control, optimism, self-esteem, andsocial relationships with family and friends. We also found that these cognitive and socioemotional benefits areassociated with greater computer use over time. In contrast to studies showing that computer use promotedsedentary lifestyles or adverse physical health outcomes, we instead found that computer use longitudinallypredicted better self-reported physical and mental health and reduced functional disabilities. The current findings attest to the promising benefits of computer use in promoting healthy cognitive and socioemotional functioning across midlife and old age.